Definition of ubiquitination modulator COP1 as a novel therapeutic target in human hepatocellular carcinoma - Lee, Yun-Han (2010)
Development of targeted therapeutics for hepatocellular carcinoma (HCC) remains a major challenge. The ubiquitination modulator COP1 regulates p53 activity by ubiquitination and it is frequently overexpressed in human HCC. In this study we tested the hypothesis that COP1 blockade by siRNA-mediated inhibition could affect the course of HCC progression. The COP1 isoform COP1-1 was selected as the most effective target for siRNAs in terms of growth inhibition and apoptotic induction in several HCC cell lines. Growth inhibition occurred in HCC cells that retained wild-type p53 or expressed mutant p53 (Y220C or R249S), whereas p53 null Hep3B cells were resistant. Microarray expression analysis revealed that the anti-proliferative effects of COPI-1 blockade were driven by a common subset of molecular alterations including a p53-associated functional network. In an orthotopic mouse xenograft model of HCC, systemic delivery of a modified COP1 siRNA by stable nucleic-acid-lipid particles (SNALP) suppressed neoplastic growth in liver without unwanted immune responses. Our findings offer a first proof of principle that COP1 can be a promising target for systemic therapy of HCC.